The family Cavognathidae (Coleoptera: Cucujoidea) in Argentina and adjacent countries - Iorio, Osvaldo Di; Turienzo, Paola (Zootaxa, 2016)
The family Cavognathidae (Coleoptera: Cucujoidea) in Argentina is represented by three species of the genus Taphropiestes Reitter, 1875: T. fusca Reitter, 1875 [Chubut], T. magna Ślipiński & Tomaszewska, 2010 [Río Negro; Chubut], and T. plaumanni Ślipiński & Tomaszewska 2010 [Buenos Aires]. A total of 2565 larvae (multiple instars), 83 pupae, 2028 live adults, and 16 dead adults of T. plaumanni were found in Argentina between 2005 and 2013 in the nests of birds representing the families Columbidae, Emberizidae, Falconidae, Furnariidae, Hirundinidae, Mimidae, Passeridae, Psittacidae, Troglodytidae and Tyrannidae. The adults were most abundant in closed mud nests of Furnarius rufus (Gmelin, 1788) [Furnariidae] and its inquiline birds, but the larvae were most abundant in wood nest boxes. When T. plaumanni was scarcely represented in bird nests from some localities, Alphitobius diaperinus (Panzer, 1797), an exotic darkling beetle [Col.: Tenebrionidae: Tenebrioninae], and one native species, Phobelius crenatus Blanchard, 1842 [Col.: Tenebrionidae: Lagriinae], were most abundant in stick nests of Furnariidae. In contrast, when A. diaperinus and P. crenatus were absent in one locality from the province of Buenos Aires, T. plaumanni was the most abundant beetle. A complete account of data is provided for these collections of T. plaumanni in Argentina. Known distributional data for all Argentinian species of Taphropiestes are plotted on maps with biogeographical provinces indicated.